Rest API automation with Rest Assured : novice to ninja (Packt Publishing, 2018)
"REST Assured is a powerful set of APIs used to automate RESTful APIs/RESTful Web services (just like Selenium WebDriver for Web applications). Almost all web applications use REST APIs to communicate with the back-end and it has gained a lot of popularity in modern-day application architecture. It is very important for QA/automation engineers to understand how to automate REST API tests. Automating REST API tests is crucial for projects because REST API tests are quick to run and more stable, unlike web automation. 90% of the IT industry is now moving towards REST API Automation. We assume that students have no experience in automation/coding and start every topic from scratch. Examples are taken from testing real-time hosted REST APIs to understand how different components can be automated, to give you an idea of industry-level frameworks and to give you confidence."--Resource description page